Ethical imperatives as parameters of influence on advantages distribution of entropy thresholds of educational process subjects - Гуз, Ю. Т.; Прохоренко, І. В (Eastern-European Journal of Enterprise Technologies, 2009)
Considering that thinking as the category is based not on classical two-place and even not multicomponent logic, and on the logician with fuzzy values of true and fuzzy rules of an exit, in work it is offered to subordinate typical consistency with making decision of subjects and groups of subjects by entropy introduction as sizes interconnecting all influence factors on alternative of functions of advantages for data accessing by transformation of resources of training subjects